Capsaicin Protects Mice from Community-Associated Methicillin-Resistant Staphylococcus aureus Pneumonia - Qiu, Jiazhang (Public Library of Science, 2012)
BACKGROUND: α-toxin is one of the major virulence factors secreted by most Staphylococcus aureus strains, which played a central role in the pathogenesis of S. aureus pneumonia. The aim of this study was to investigate the impact of capsaicin on the production of α-toxin by community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) strain USA 300 and to further assess its performance in the treatment of CA-MRSA pneumonia in a mouse model. METHODOLOGY/PRINCIPAL FINDINGS: The in vitro effects of capsaicin on α-toxin production by S. aureus USA 300 were determined using hemolysis, western blot, and real-time RT-PCR assays. The influence of capsaicin on the α-toxin-mediated injury of human alveolar epithelial cells was determined using viability and cytotoxicity assays. Mice were infected intranasally with S. aureus USA300; the in vivo protective effects of capsaicin against S. aureus pneumonia were assessed by monitoring the mortality, histopathological changes and cytokine levels. Low concentrations of capsaicin substantially decreased the production of α-toxin by S. aureus USA 300 without affecting the bacterial viability. The addition of capsaicin prevented α-toxin-mediated human alveolar cell (A549) injury in co-culture with S. aureus. Furthermore, the in vivo experiments indicated that capsaicin protected mice from CA-MRSA pneumonia caused by strain USA 300. CONCLUSIONS/SIGNIFICANCE: Capsaicin inhibits the production of α-toxin by CA-MRSA strain USA 300 in vitro and protects mice from CA-MRSA pneumonia in vivo. However, the results need further confirmation with other CA-MRSA lineages. This study supports the views of anti-virulence as a new antibacterial approach for chemotherapy.